Study of cells attachment using impedance spectroscopy technique - Nordin, Anis Nurashikin; S.M., Arifuzzaman; Mel, Maizirwan; Spray, David; Voiculescu, Ioana (2011)

(untitled)
In this paper we report on the electrical impedance spectroscopy characterization of the attachment of two mammalian cell lines: endothelial cells (RFPEC) and fibroblast cells (V79). For electrical cell–substrate impedance sensing (ECIS) of the endothelial cells a commercially available eightwell cell culture impedance array (ECIS-8W1E) was used. The impedance measurements were recorded with cell culture medium (without cells) and with endothelial cells or fibroblast cells in the culture medium over a frequency range from 100 Hz to 100 kHz. The impedance measurements were compared to the equivalent circuit model. The impedance measurements were also simulated using COMSOL Multiphysics, a commercially available modeling package.